Realizing high power factor and thermoelectric performance in band engineered AgSbTe2 - Yu Zhang; Congcong Xing; Dongyang Wang; Aziz Genç; Seng Huat Lee; Cheng Chang; Zhi Li; Luyao Zheng; Khak Ho Lim; Hangtian Zhu; Rabeya Bosry Smriti; Yu Liu; et al. (Nature Communications)
Abstract AgSbTe2 is a promising p-type thermoelectric material operating in the mid-temperature regime. To further enhance its thermoelectric performance, previous research has mainly focused on reducing lattice thermal conductivity by forming ordered nanoscale domains for instance. However, the relatively low power factor is the main limitation affecting the power density of AgSbTe2-based thermoelectric devices. In this work, we demonstrate that hole-doped AgSbTe2 with Sn induces the formation of a new impurity band just above the valence band maximum. This approach significantly improves the electrical transport properties, contrary to previous strategies that focused on reducing lattice thermal conductivity. As a result, we achieve a record-high power factor of 27 μWcm−1K−2 and a peak thermoelectric figure of merit zT of 2.5 at 673 K. This exceptional performance is attributed to an increased hole concentration resulting from the formation of the impurity band and a lower formation energy of the defect complexes ( $${V}_{Ag}^{1-}$$ V A g 1 − + $${Sn}_{Sb}^{1-}$$ S n S b 1 − ). Besides, the doped materials exhibit a significantly improved Seebeck coefficient by inhibiting bipolar conductivity and preventing the formation of n-type Ag2Te. Additionally, the optimized AgSbTe2 is used to fabricate a unicouple thermoelectric device that achieves energy conversion efficiencies of up to 12.1% and a high power density of 1.13 Wcm−2. This study provides critical insights and guidance for optimizing the performance of p-type AgSbTe2 in thermoelectric applications.